Laparoscopic radical nephrectomy with inferior vena cava thrombectomy: A combined retroperitoneal and transperitoneal approach. Issue 2 (May 2020) - Giannubilo, Willy; Sortino, Giuseppe; Diambrini, Maurizio; Di Biase, Manuel; Marconi, Andrea; Ferrara, Vincenzo
Renal cell carcinoma with inferior cava thrombus indicates biologically aggressive cancer, so the complete surgical resection remains standard of care with best long-term outcomes. Laparoscopic radical nephrectomy with vena cava thrombectomy represents nowadays a mini-invasive surgical alternative to the classic open nephrectomy. We present the case of a patient with incidental diagnosis of a right renal mass with level II inferior cava thrombus completely managed with both retroperitoneal and transperitoneal approaches. The use of a double access was planned to ensure a safe and complete vascular control. In our opinion, optimal patient selection, extensive laparoscopic experience, and knowledge of both transperitoneal and retroperitoneal approaches are critical elements for the safe application of this technique, although this procedure remains challenging and technically demanding.